Energy Conservation and Carbon Flux Distribution During Fermentation of CO or H2/CO2 by Clostridium ljungdahlii - Zhu, Hai-Feng; Liu, Zi-Yong; Zhou, Xia; Yi, Ji-Hong; Lun, Zeng-Min; Wang, Shu-Ning; Tang, Wen-Zhu; Li, Fu-Li (Frontiers in Microbiology, 2020)
Both CO and H2 can be utilized as energy sources during the autotrophic growth of Clostridium ljungdahlii. In principle, CO is a more energetically and thermodynamically favorable energy source for gas fermentation in comparison to H2. Therefore, metabolism may vary during growth under different energy sources. In this study, C. ljungdahlii was fed with CO and/or CO2/H2 at pH 6.0 with a gas pressure of 0.1 MPa. C. ljungdahlii primarily produced acetate in the presence of H2 as an energy source, but produced alcohols with CO as an energy source under the same fermentation conditions. A key enzyme activity assay, metabolic flux analysis, and comparative transcriptomics were performed for investigating the response mechanism of C. ljungdahlii under different energy sources. A CO dehydrogenase and an aldehyde:ferredoxin oxidoreductase were found to play important roles in CO utilization and alcohol production. Based on these findings, novel metabolic schemes are proposed for C. ljungdahlii growing on CO and/or CO2/H2. These schemes indicate that more ATP is produced during CO-fermentation than during H2-fermentation, leading to increased alcohol production.